2015
DOI: 10.7567/apex.8.027301
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of sound radiation pattern via gradient acoustic metasurface with space-coiling structure

Abstract: We designed, fabricated, and experimentally demonstrated a gradient acoustic metasurface to manipulate sound radiation patterns. The gradient metasurface is constructed on the basis of a coiling-up space in a tunable interdigitated structure, which exhibits relative refractive index in a discretized classic hyperbolic secant profile. Capable of generating secondary sound sources with desired gradient phase shifts, the metasurface shows the ability of controlling sound radiation such as by cylindrical-to-plane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
71
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 26 publications
2
71
1
1
Order By: Relevance
“…Much effort has been devoted to reducing the impact of mismatched impedance. 6,8,9,11,15,20,[22][23][24][25][26][27][28][29] One way to do so is to utilize Fabry-Perot (FP) resonances, 6,8,15,20,22,29 which can increase the transmission energy because of the destructive interference between the multiple reflections of acoustic waves on the input and output surfaces of the acoustic lens. Because the resonant frequency of FP resonances is sensitive to the effective thickness of the acoustic lens, it may not be able to perfectly eliminate the reflection in real applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Much effort has been devoted to reducing the impact of mismatched impedance. 6,8,9,11,15,20,[22][23][24][25][26][27][28][29] One way to do so is to utilize Fabry-Perot (FP) resonances, 6,8,15,20,22,29 which can increase the transmission energy because of the destructive interference between the multiple reflections of acoustic waves on the input and output surfaces of the acoustic lens. Because the resonant frequency of FP resonances is sensitive to the effective thickness of the acoustic lens, it may not be able to perfectly eliminate the reflection in real applications.…”
mentioning
confidence: 99%
“…Space-coiling structures have been utilized in the design of gradient acoustic lenses. [6][7][8][9][10] With gradient acoustic lenses, acoustic radiation patterns, such as focusing, 6,[8][9][10][11] tunable transmission, 7,12,13 reflection, 10 and cylindrical-to-plane wave conversion, 9 can be manipulated. Very recently, acoustic meta-surfaces have been used in the design of acoustic lenses.…”
mentioning
confidence: 99%
“…These labyrinthine structures have shown fascinating properties (20)(21)(22)(23)(24) including negative and zero effective refractive indices. Anomalous reflection and refraction have been both numerically (25,26) and experimentally (27)(28)(29)(30)(31) demonstrated with labyrinthine units based on phase discontinuities. For completeness, we note that acoustic metasurfaces based on impedance discontinuities (as opposed to phase discontinuities) have also been theoretically demonstrated (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some researchers have demonstrated that the structure of coiling-up space or subwavelength corrugated surface can be used to design AMS with the phase change covering 0∌2π range. [12][13][14][15][16][17][18][19][20][21][22] And then some novel phenomena are demonstrated, such as the anomalous reflection and refraction, [12][13][14][15][16][17][18] and the planar acoustic axicon and lens. [19][20][21][22] Ding et al 23,24 have proposed that the split hollow sphere and double-split hollow sphere, as acoustic resonator, can be also used to construct AMS.…”
Section: Introductionmentioning
confidence: 99%